ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK REKLAME DI EKS KARESIDENAN SEMARANG - Yulianto Harjono, 10.05.52.0105 (Students Journal of Accounting and Banking, 2013)
Source of regional income derived from the regional it self. One of the source regional income is tax advertisement income. This research are purposed to analyze the effect of tax payers advertisement, sum of industry, PDRB, and inflation toward advertisement income.This research used data on period 2005 until 2011 in ex karesidenan Semarang, that are Semarang city, kabupaten Semarang, salatiga city, kabupaten Demak and Kabupaten Kendal.Technique used is regression analysis with classic assumption.The result shows that: (1) Tax payers advertisement have positive and significant effect toward advertisement income. (2) Sum of industry have positive and significant effect toward advertisement income. (3) PDRB have positive and significant effect toward advertisement income. (4) Inflation have positive and significant effect toward advertisement income. The suggestion are: (1) The government should pay attention for factors affect advertisement taxpayers, such as tax payers advertisement, sum of industry, PDRB, inflation because proved empirically affect the advertisement income. (2) The government should implement the advertisement tax based on the inlfation rate so did not make the tax payer pay higher.Keywords: tax payers advertisement, sum of industry, PDRB, inflation, and advertisement income.